Geometric algorithms for creating ornamental fillings in computer design of stained glass - Петрушевський, Андрій Олександрович (Technology audit and production reserves, 2014)
The importance and basic types of ornamental stained glass filling and its most common historical schemes are described in the paper. Historical factors of stained glass technique and the main stylistic features in the regional-historical context were disclosed. The basic geometric algorithms for creating the majority of the most commonly used ornamental fillings, needed to design artistic two-dimensional stained glass, and the means of their parametric setting in computer design of stained glass panels were determined. Design of two-dimensional stained glass panel by traditional methods is rather laborious and time-consuming process. Often, several experts were involved in these projects. For example, draftsman, glass engraver and glass-artist, who knows the assembly peculiarities of the panel. In the case of ornamental filling, sometimes mathematical calculations, applied in each case individually were enough. In the case of developing a computer design system, such a project will be created by setting up several parameters. As a result of the studies, geometric algorithms to obtain the scheme of connecting grid for the basic styles of ornamental filling of stained panel were designed. Such technology will significantly reduce the project creation time and greatly expand the range of users, even those not familiar with the peculiarities of the stained glass technique, such as designers, architects and artists.